Long intervals between two doses of HPV vaccines and magnitude of the immune response: a post hoc analysis of two clinical trials - Vladimir Gilca; Chantal Sauvageau; Gitika Panicker; Gaston De Serres; John Schiller; Manale Ouakki; Elisabeth R. Unger (Taylor & Francis Group, 2019)
The objective of this analysis was to compare the anti-HPV GMTs and their distribution after a 6-month or a 3-8 -y interval between two HPV vaccine doses. The results from two clinical trials, conducted by the same team in the same region, with serological assays performed at the same laboratory using the same ELISA methodology were compared. In the first study, 173 9-10-y-old girls and boys received two doses of 9vHPV vaccine at a 6-month interval; in the second study, 31 girls vaccinated with one dose of 4vHPV at the age of 9-14 y received a dose of 9vHPV 3-8 y later (mean 5.4 y). In both studies, blood samples were collected before and 1 month post second dose. Despite large differences in the time since the first dose, all subjects (100%) were seropositive to the common 4 HPV types (6, 11, 16 and 18) to both vaccines, with comparable GMTs and titer distributions before the second dose. One month post second dose, the GMTs increased 40-91-fold for those with a 6-month interval between doses and 60-82-fold for those with a 3-8-y interval. Titer distributions after the booster dose were comparable in the two studies. These results indicate that 2-dose HPV vaccination schedules with an interval of several years could be used for pre-adolescents. Intervals longer than 6 months may facilitate logistics for immunization programs and could be useful during periods of vaccine shortage or as a transition while the effectiveness of a one-dose schedule is being evaluated.